Traditional fermented anchovy rusip demonstrates antidiabetic effects through enzyme inhibition and metabolic improvement in diabetic rats - MUHAMMAD ALFID KURNIANTO; ALFINA AYU PUSPITA; SRI WINARTI; HADI MUNARKO; SALMA SHAFRINA AULIA; DINA MUSTIKA RINI (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Kurnianto MA, Puspita AA, Winarti S, Munarko H, Aulia SS, Rini DM. 2025. Traditional fermented anchovy rusip demonstrates antidiabetic effects through enzyme inhibition and metabolic improvement in diabetic rats. Biodiversitas 26: 2278-2288. Rusip, a traditional fermented anchovy, is a high-protein food with potential anti-diabetic properties. This study investigated the physicochemical properties and in vitro inhibitory activity of diabetes-related enzymes of rusip fermented at different time points (0, 7, 14, and 21 days). The optimal formulation was then subjected to further in vivo study with Streptozotocin-Nicotinamide (STZ-NA)-induced rats. The results revealed increased moisture, soluble protein, TVBN, and N-amino acid and decreased protein, fat, ash, carbohydrate, and pH of rusip during the 21-day fermentation time compared to the other fermentation stages. Glutamic acid and arginine, as well as Methyl-cis-10-pentadecenoate and Methyl-cis-4,7,10,13,16,19-docosahexaenoate, were the most dominant amino acids and fatty acids in rusip. The rusip showed ?-glucosidase (53.8-59.8%) and ?-amylase (40.3-46.7%) inhibitory activities at 20 mg/mL, with the lowest IC50 observed at day 14 of fermentation (30.52 mg/mL and 26.01 mg/mL). Further evaluation in STZ-NA-induced diabetes rats showed that rusip administration could reduce fasting blood glucose, HbA1c, and HOMA-IR and improve insulin levels, HOMA-B and QUICKI. Hepatoprotective (suppressing elevated AST, ALP, and ALT) and nephroprotective (decreasing urea and creatinine) effects were also observed. Rusip also improved lipid metabolism, reducing LDL, triglyceride, and cholesterol levels and returning HDL levels to normal, thereby reducing hypercholesterolemia. These findings suggest that rusip may mitigate diabetes-related metabolic disorders, highlighting its potential as a functional food for diabetes management.